Pengaruh Variasi Cairan Pendingin terhadap Keausan Pahat HSS dan Struktur Mikro Pembubutan Baja ST 42 - Prakosa, Gilang Satria; Mufarida, Nely Ana; Bahri, Mokh Hairul (Fakultas Teknik UMSU, 2025)
This study aims to determine the effect to coolant variation on the wear level of High Speed Steel (HSS) cutting tools and the microstructural changes after the turning process of ST 42 steel. An experimental method was employed using a conventional lathe. The coolant variations used include: 30% coolant with 70% water, 50% coolant with 50% water, 100% water and dry cutting (no coolant). The cutting parameters were set at a spindle speed of 382 rpm, cutting speed of 30 m/min, feed rate of 0.03 mm/min and depth of cut 1 mm. Tool wear was measured using a caliper and microstructural analysis was conducted using an optical microscope. The result showed that the 50% coolant with 50% water mixture yielded the lowest tool wear (0.2 mm), while the absence of coolant resulted in the highest wear (0.73 mm). Microstructural analysis also indicated that balance coolant mixture was more effective in maintenance the tool’s microstructure. The use of coolant effectively reduced tool wear and preserved machining quality during the turning process.